Pendampingan Kompetensi SDM BUMDes dan Pelaku UMKM untuk Meningkatkan Jejaring Usaha Unit Usaha Pengelolaan Sampah BUMDes Perkasa Sindangsuka: Assistance with HR Competence of BUMDes and MSME Entrepreneurs to Improve Business Networks of Waste Management Business Units at BUMDes Perkasa Sindangsuka - Muizu, Wa Ode Zusnita; Rahma, Hilwa Delia; Oktaviani, Oktaviani; Subana, Fairuz Axioma; Gloriana, Citra; Ramadhani, Muhammad; Pratama, Naufal Aqillah; Permana, Aji Indra; Putri, Puspa Aulia; Dzaky, Muhammad Fathan; Fajrin, Arini Nurul; Sylandra, Rafiska; Raffa, Muhammad; Cahyani, Nabila Rizqi; Firdaus, Yoga Firman; Maharani, Adinda Yulia; Auranissa, Dhea; Solikhah, Siti Mar’atus; Safitri, Aisyah Junisah; Triski, Dara Sagita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Padjadjaran University KKN-PPM program was implemented in Sindangsuka Village in the period 02 July to 02 August 2024. A total of eighteen students from various departments at Padjadjaran University were actively involved in this program with a focus on increasing the capacity of local BUMDesa Human Resources (HR). This activity was motivated by Padjadjaran University's concern for the social and economic problems of the surrounding community, as well as efforts to encourage the application of the concept of entrepreneurship at the village level. The main object of KKN-PPM activities this time is BUMDesa Sindangsuka, Cibatu District, Garut Regency, especially the Waste Management Unit. By holding a focus group discussion activity with the title "From Discussion to Action: Turning Waste into Blessings" the event resulted in an in-depth understanding of the techniques and competencies needed to run this business unit.